(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article addresses the issues of housing provision for military personnel, analyzes the main challenges they face, and identifies possible directions for solving existing problems. The purpose of the article is to determine the features of housing provision for military personnel. It is emphasized that the housing provision for military personnel and their families in Ukraine is carried out by the Ministry of Defense through several mechanisms, including new construction, monetary compensation, and the conversion of non-residential premises. The need for reforming the housing provision system and introducing new mechanisms, such as special savings programs, leasing, and mortgages, to increase housing availability for military personnel is highlighted. Special attention is given to the need to adapt the legislative framework to effectively meet the needs of military personnel. The article outlines ways to improve housing conditions for military personnel through innovative and legislative approaches aimed at the long-term sustainability of housing policy in the context of their social protection. It is noted that due to martial law, traditional methods of housing provision for military personnel have proven ineffective, which necessitates new approaches and scientific research to develop sustainable solutions in this field. Special attention is required for controlling the formation of housing queues, the accounting and distribution of housing, as well as contractual activities with commercial entities regarding housing construction. It is emphasized that the problem is complicated by the bureaucratization of the system, although the state is striving to simplify procedures. Moreover, the need to adapt housing provision mechanisms is particularly relevant given the socio-economic challenges faced by the country, which require adequate funding and consideration of the specific status of military personnel. It is identified that promising directions for further scientific research include determining sufficiency and accessibility requirements for military personnel’s housing.